KEMAMPUAN MAHASISWA SEBAGAI CALON GURU BIMBINGAN DAN KONSELING DALAM MEMNYUSUN PROGRAM BK (Studi terhadap Angkatan 2010 STKIP PGRI SUMBAR) - Vandini, Novia; Kasih, Fitria; Wira Nita, Rahma (Bimbingan dan Konseling, 2013)
The problem in this research based on phenomena that researcher found in the field, some of college students as guidance and counseling teacher candidate have difficulty to compose guidance and counseling program, so that researcher interest to solve this problem about ability of guedance and counseling teacher candidate to compose their guidance and counseling program (study at collage student 2010 of STKIP PGRI west sumatera). The purpose of this research to describe: (1) knowledge of student to compose guidance and counseling program. (2) student aptitude in compose guidance and counseling program.This research was descriptive research that try to describe the way thing are. The population in this research was all collage student 2010 of STKIP PGRI west sumatera. The amount of population was 321 student. Technique to take the sample in this research use random sampling. Random sampling is one of technique to take the sample randomly without care about level of population, so that the sample in this research became 36 students. Instrument that researcher use was quetionare, meanwhile to analize the data researcher use percentage technique.The result of this reserch describe that: (1) knowledge of students to compose guidance and counseling program was pour category. (2) student aptitude in compose guidance and counseling program was enough category. Based on researcher research, researcher suggest for guidance and counseling teacher candidate to improve their ability in manage guidance and counseling program, for the lecturer its hoped for them to guide the college students guidance and counseling candidate to the field, and make sure the students were realy have guidance and counseling program before go into the field, and for next researcher can develope this research more extend and give more significance. Â Â